2020
DOI: 10.3390/v12020193
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of CRISPR and Marker-Based Methods for the Engineering of Phage T7

Abstract: With the recent rise in interest in using lytic bacteriophages as therapeutic agents, there is an urgent requirement to understand their fundamental biology to enable the engineering of their genomes. Current methods of phage engineering rely on homologous recombination, followed by a system of selection to identify recombinant phages. For bacteriophage T7, the host genes cmk or trxA have been used as a selection mechanism along with both type I and II CRISPR systems to select against wild-type phage and enric… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(28 citation statements)
references
References 58 publications
0
28
0
Order By: Relevance
“…Previous reports had indicated that OmpF serves as a secondary receptor to T2 (in addition to the primary receptor FadL) [127] and Cytidine monophosphate kinase (encoded by cmk) is an essential host factor in T7 phage infection [50]. Our genome-wide screens did not recapitulate these findings probably because these mutants provide an intermediate fitness in the presence of phages [128] and are swept from the population in the presence of highly resistant phage receptor mutations.…”
Section: A Crispri Screen Provides Deeper View Of Phage Resistance Dementioning
confidence: 55%
“…Previous reports had indicated that OmpF serves as a secondary receptor to T2 (in addition to the primary receptor FadL) [127] and Cytidine monophosphate kinase (encoded by cmk) is an essential host factor in T7 phage infection [50]. Our genome-wide screens did not recapitulate these findings probably because these mutants provide an intermediate fitness in the presence of phages [128] and are swept from the population in the presence of highly resistant phage receptor mutations.…”
Section: A Crispri Screen Provides Deeper View Of Phage Resistance Dementioning
confidence: 55%
“…We also did not observe significant fitness scores for host factors that may bias the rate of lysogeny of the two temperate phages (186 and P2), leading to resistance of those lysogens. Our genome-wide screens did not recapitulate these findings probably because these mutants provide an intermediate fitness in the presence of phages [134] and are swept from the population in the presence of highly resistant phage receptor mutations.…”
Section: Plos Biologymentioning
confidence: 86%
“…The editing of virulent phage genomes has remained a major challenge for phage engineering, largely due to the lack of universally applicable genetic tools or reliance on a native CRISPR-Cas system 25,26,28,[46][47][48][49][50] . While the introduction of foreign gene content into phages is relatively straightforward to perform with homologous recombination (HR), ultimately the selection or screening for these rare recombinants is limiting even in well characterized phages 48 .…”
Section: Cas13amentioning
confidence: 99%